El abuso de poder de mercado y el lavado de activos en el Ecuador - Ramírez Erazo, Pablo Efraín (2025)
The so-called money laundering is presented as a global concern that affects the financial system of each country by virtue of the implications generated by the possible manipulation of the different aspects of the economy and that significantly harm the development of the countries, violating various legal assets. Money laundering has a cover-up character that violates not only the socioeconomic order, but also breaks the necessary legal nature of all the goods circulating in the market, the stability and solidity of the financial system and free competition. Given the negative consequences of this crime, what is the relationship between the abuse of market power and money laundering in Ecuador is formulated as an investigation problem? And the approach of the general objective is to determine the relationship between the abuse of market power and money laundering in Ecuador. With the use of a review and documentary analysis, the elements of connection between the crime of money laundering and the abuse of market power are identified, particularly by the execution of the practice of setting predatory or exploitative prices. It is concluded that this relationship that harms consumers, the market and the country's economy in general is verified in practice.